The Impact of Feedback and Explicit Rhetorical Instruction on EFL Students’ Writing Proficiency in Higher Education - Luisa María González Rodríguez; Pedro Álvarez Mosquera (Atlantis, 2020)
The efficacy of feedback on EFL students’ writing proficiency has been researched extensively and has also sparked off considerable controversy among detractors and supporters alike. However, there is still room for further investigation on how feedback can better contribute to students’ writing performance and how it can be fully integrated into the learning process. This article empirically demonstrates the learning advantages of combining both feedback and explicit rhetorical instruction for improving EFL students’ writing skills in the context of higher education. In a longitudinal study of the rhetorical competence of students’ written production carried out over a semester, three treatment variables were investigated: the effect of feedback, the effect of explicit instruction and the combination of both, along with a control condition of no treatment at all. Students were allocated to a treatment group on the basis of their attendance and work profile and the results of the analysis of the written production of each group were compared. The findings confirm not only that the group that received the combined treatment achieved higher grades and displayed a better control of relevant microskills in their written production, but also that neither feedback nor explicit instruction alone proved as effective in terms of rhetorical competence as the combination of the two variables.